Barkskins : a novel - Proulx, Annie (New York : Scribner, an imprint of Simon & Schuster, Inc., 2016)
In New France in the late 18th century, Rene Sel, an illiterate woodsman makes his way from Northern France to the homeland to seek a living. This novel tells stories of Rene's children, grandchildren, and great grandchildren, as well as the descendants of his friends and foes, as they travel back to Europe, to China, to New England, always in quest of a livelihood or fleeing stunningly brutal conditions--war, pestilence, Indian attacks, the revenge of rivals.
Includes family trees.
Keywords: Families -- Fiction; Canada -- Fiction; New France -- Fiction; Epic fiction